Community-based models of mobility training after stroke: a scoping review - Toluwalase Ayokunle Ayelabowo; Temitope Christianah Ajayi; Stephen Hsiao-Feng Macdonald (Bulletin of Faculty of Physical Therapy)
Abstract Background Irrespective of the severity, survival of a stroke has become commonplace, but many experience long-term physical, cognitive, and emotional difficulties, with walking difficulties being a frequent challenge. The community-based model of gait training is an innovative and holistic approach to neurorehabilitation that focuses on restoring mobility and enhancing the overall quality of life of stroke survivors. Aims To assess the impact of community-based stroke rehabilitation programs from existing literatures. Objectives To identify community-based stroke rehabilitation programs that are effective in improving function in stroke survivors. Methods We conducted a scoping review of peer-reviewed articles to understand the impact of the community-based rehabilitation model of mobility training after stroke. We searched five different databases: PsycINFO, PubMed, CINAHL complete, Embase, and SCOPUS using topic-specific keywords. Only studies published in the English language from 2013 to 2023 were included. Results Thirty-five articles met the inclusion criteria. Mobility training using either a treadmill or overground surfaces improved mobility. Orthotics use improved gait and balance among stroke survivors. Adapted video games for rehabilitation improved gait speed, balance, and mobility while the use of transcutaneous electrical nerve stimulation (TENS) aided functional recovery. The use of music or sound incorporated with exercises improved mobility, gait speed, and balance. Engaging in group exercises improved walking capacity, balance, walking speed, cardiovascular function, and community integration. Conclusion Some community-based rehabilitation programs are effective in improving the physical and social recovery of stroke survivors. This concept can be considered when planning a recovery program for stroke survivors who do not have the ability to access a hospital rehabilitation setting.